Development of a loop-mediated isothermal amplification assay for the rapid detection of Russula subnigricans and Russula japonica - Long, Pan; Jiang, Zijuan; He, Zhengmi; Chen, Zuohong (Frontiers in Microbiology, 2022)
Russula subnigricans is the only deadly species in the genus Russula with a mortality rate of more than 50%, and Russula japonica is the most common poisonous species, making rapid species identification in mushroom poisoning incidents extremely important. The main objective of this study was to develop a rapid, specific, sensitive, and simple loop-mediated isothermal amplification (LAMP) assay for the detection of R. subnigricans and R. japonica. Two sets of species-specific LAMP primers targeting internal transcribed spacer (ITS) regions were designed to identify R. subnigricans and R. japonica. The results demonstrated that while LAMP could specifically detect R. subnigricans and R. japonica, the polymerase chain reaction (PCR) could not distinguish R. subnigricans from Russula nigricans. In addition, the results demonstrated that, compared to electrophoresis-LAMP and real-time quantitative LAMP (RT-qLAMP), the detection sensitivity of HNB-LAMP (a mixture of LAMP with hydroxy naphthol blue (HNB) dye) for R. subnigricans could reach 0.5 pg/μl and was 100-fold higher than that of PCR. The LAMP reaction could be completed in 45 min, which is much faster than the conventional PCR. In the future, LAMP can be used a quick, specific, and sensitive detection tool in various fields.